Utility of the phalangeal ultrasonometry in the assessment of osteoporosis risk - Bolanowski, Marek; Pluskiewicz, Wojciech; Jawiarczyk, Aleksandra (Menopause Review/Przegląd Menopauzalny, 2005)
Objectives: Quantitative ultrasound can be used for the assessment of skeletal status and fracture risk in postmenopausal women. Materials and methods: Analysis of amplitude dependent speed of sound (Ad-SoS) ultrasound transmission through the epiphyses of hand phalanges was carried out in 83 women (38 premenopausal and 45 postmenopausal) using apparatus Sonic 1200 (IGEA, Carpi, Italy). Results: The values of Ad-SoS were comparable with those observed in other populations, greater in premenopausal than postmenopausal women. A positive correlation between Ad-SoS and height (r=0.36, p<0.052), and negative ones between Ad-SoS and BMI (r=-0.46, p<0.05), and between Ad-SoS and age (r=-0.70, p<0,05) were observed in the entire group. In the postmenopausal subjects there was negative correlation between Ad-SoS and age (r=-0.46, p<0.05). In premenopausal women negative correlations between Ad-SoS and age (r=-0.46, p<0.05), and Ad-SoS and BMI (r=-0.73, p<0.05) were shown. Conclusions: 1. Quantitative ultrasound of the hand phalanges is an useful screening method for the assessment of bone quality. 2. Ad-SoS values are lower in the postmenopausal women than in premenopausal ones. Negative correlation of Ad-SoS and age reflects faster bone loss after the manopause due to loss of estrogen protective activity. 3. Positive correlation of Ad-SoS and height, and a negative one with BMI show the relation of the bone structure and quality from skeletal size.